Linking Job Engagement To Employee Performance: The Roles Of Work Commitment And Transformational Leadership - Wayan Santika (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study examines the influence of transformational leadership on the performance of personnel of the Directorate of Special Criminal Investigation, with work attachment and work commitment as explanatory variables, as well as work commitment as a reinforcement of leadership and performance relationships. The researcher uses a quantitative approach with explanatory design and survey methods. The researchers collected data from one hundred and twenty respondents through a closed-ended questionnaire based on a five-point Likert scale, ranging from strongly disagree to strongly agree. The researcher compiled the instrument by adapting indicators from previous research, then conducted validity and reliability tests so that each item measured the construct consistently. The researcher analyzed the data using SEM PLS with the latest version of SmartPLS through the evaluation of measurement models and structural models. The results of the analysis show that transformational leadership does not have a significant direct influence on performance. Work attachment has a positive and significant influence on performance, and is the main driver for the formation of work commitments. Work commitment also has a positive and significant influence on performance, so commitment plays an important role as an important pathway that connects work attachment and performance. Interaction testing confirms work commitment reinforces the influence of transformational leadership on performance, so that leadership impacts appear more clearly when personnel are highly committed. These findings place work attachment as the focus of interventions to strengthen commitment, maintain consistency in work according to procedures, and encourage performance achievement in a work environment that demands discipline and operational targets.